2007
DOI: 10.1002/ejsp.379
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance expectancies in stereotypic domains: task relevance and the reduction of stereotype threat

Abstract: The experiments presented here extend previous research on reducing stereotype threat, along with examining the mediating role of performance expectancies. Women who generated shared academic characteristics between men and women predicted higher scores for themselves on a math test compared to the baseline and those who generated shared non-academic characteristics or shared physical characteristics. No effects were found for male participants' performance expectancies on an English test. Extending the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 39 publications
0
26
0
2
Order By: Relevance
“…In future research, it could be interesting to explore other strategies for reducing age-related stereotype threat in the organizations. This issue could be related to recent work by Rosenthal and Crisp (2006;Rosenthal, Crisp, & Suen, 2007) documenting reduced stereotype threat effects among women who thought about characteristics shared (i.e., similarities) between men and women. For example, future research could compare the consequences of organizational interventions designed to activate similarities between older and younger workers on older worker's aspirations and performance in the work domain with the effects of the activation of negative or positive age-related stereotypic information.…”
Section: Discussionmentioning
confidence: 86%
“…In future research, it could be interesting to explore other strategies for reducing age-related stereotype threat in the organizations. This issue could be related to recent work by Rosenthal and Crisp (2006;Rosenthal, Crisp, & Suen, 2007) documenting reduced stereotype threat effects among women who thought about characteristics shared (i.e., similarities) between men and women. For example, future research could compare the consequences of organizational interventions designed to activate similarities between older and younger workers on older worker's aspirations and performance in the work domain with the effects of the activation of negative or positive age-related stereotypic information.…”
Section: Discussionmentioning
confidence: 86%
“…That is, female participants who completed a shared characteristics task-which served to minimize perceived gender differences and undermine self-categorization-chose less stereotypical careers and completed more math questions correctly than participants in a control condition. Rosenthal, Crisp, and Suen (2007) demonstrated that this effect was even more pronounced when the shared characteristics were relevant to the stereotyped domain, suggesting that undermining self-categorization may be particularly key when the situation activates the relevant stereotype.…”
Section: Stereotype Threat: Negative Effects Of Self-categorization Amentioning
confidence: 91%
“…Although due to limited research, little is known about the underlying mechanisms of stereotype lift, a number of underlying processes have been considered as the basis for stereotype threat, including decreased working memory (Schmader, Johns, & Forbes, 2008), prevention focus (US university students: Grimm, Markman, Maddox, & Baldwin, 2009), and performance expectancies (UK university students: Rosenthal, Crisp, & Suen, 2007). It is possible that geometric-based navigation relies on different underlying processes than landmark-based navigation, which map onto the different processes outlined as mechanisms underlying stereotype threat.…”
mentioning
confidence: 99%